Perlindungan hukum pidana terhadapa tindak kekerasan seksual di dalam institusi perguruan tinggi - Riyan Alpian (Universitas Islam Indonesia, 2022)
This study aims to determine the types of sexual violence crimes that occur in universities and legal protection for victims of sexual violence crimes in universities. This is a normative legal research that uses statutory approach and case approaches. The results showed that there were 13 types of sexual harassment that occurred in educational institutions according to Dzeich and Weine, namely the 'Power Player' type, the 'Role as a Father or Mother Figure' type, the 'Group Member' type, the 'Harassment in Closed Places' type, the 'Groper' type, the 'Opportunist' type, the 'Confidante' type, the 'Situational Harassment' type, the 'Pest' type, the 'The Great Gallant’ type, the 'Intellectual Seducer' type, the 'Incompetent' type, the 'Sexualized Environment' type. Legal protection given to victims of sexual violence in universities is regulated in Article 12 of the Minister of Education and Culture Regulation (Permendikbudristek) Number 30 of 2021 on the Prevention and Handling of Sexual Violence (PPKS) in Higher Education. In addition, Article 14 and Article 16 of the Permendikbudristek also regulate the provisions of administrative sanctions that can be imposed on perpetrators of sexual violence in universities. With regard to criminal sanctions, although the Criminal Code does not specifically regulate the crime of sexual violence, perpetrators of sexual harassment in universities can be subject to criminal sanctions as regulated in Articles 289 to 296 of the Criminal CodeKey Words: Sexual violence; victim; College; legal protectionAbstrakPenelitian ini bertujuan untuk mengetahui jenis-jenis tindak pidana kekerasan seksual yang terjadi di perguruan tinggi dan perlindungan hukum bagi korban tindak pidana kekerasan seksual di perguruan tinggi. Penelitian ini adalah penelitian hukum normatif yang menggunakan pendekatan perundang-undangan dan pendekatan kasus. Hasil penelitian menyimpulkan bahwa jenis-jenis pelecehan seksual yang terjadi di institusi pendidikan menurut Dzeich dan Weine ada 13, yaitu tipe ‘Pemain Kekuasaan’, tipe ‘Berperan sebagai Figur Ayah atau Ibu’, tipe ‘Anggota Kelompok’, tipe ‘Pelecehan di Tempat Tertutup’, tipe ‘Groper’, tipe ‘Oportunis’, ‘Confidante’, tipe ‘Pelecehan Situasional’, tipe ‘Pest’, tipe ‘The Great Gallant, tipe ‘Intellectual Seducer’, tipe ‘Incompetent’, tipe ‘Sexualized Environment’. Perlindungan hukum yang diberikan kepada para korban kekerasan seksual di perguruan tinggi diatur dalam Pasal 12 Permendikbudristek Nomor 30 Tahun 2021 tentang Pencegahan dan Penanganan Kekerasan Seksual (PPKS) di Lingkungan Perguruan Tinggi. Selain itu, Pasal 14 dan Pasal 16 permendikbudristek tersebut juga mengatur ketentuan sanksi administratif yang dapat dikenakan kepada para pelaku kekerasan seksual di perguruan tinggi. Berkaitan dengan sanksi pidana, meskipun KUHP belum secara spesifik mengatur tentang tindak pidana kekerasan seksual, pelaku pelecehan seksual di perguruan tinggi dapat dijatuhi sanksi pidana yang diatur dalam Pasal 289 hingga Pasal 296 KUHP.Kata-kata Kunci: Kekerasan seksual; korban; perguruan tinggi; perlindungan hukum